Public and Private Partnership: Innovation-Driven Growth of Agriculture at the Regional Level - DUDIN, Mihail Nikolaevich; SHAKHOV, Oleg Fedorovich; VYSOTSKAYA, Nataliya Vladimirovna; STEPANOVA, Diana Igorevna (Journal of Environmental Management and Tourism, 2020)
The purpose of this study is to define the economic context related to the functioning of the agricultural industry in the regions of the Central Federal District (CFD): the main structural sectors of the industry and its main results are described, and the main trends in the productivity and sustainability of agriculture in the region are analyzed. The results of the study indicate that investing in agricultural innovation is of great importance for improving the agricultural productivity, preserving the environment, and eradicating poverty and hunger. In the context of limited resources, a public-private partnership (PPP) can become a promising mechanism for the implementation of innovation projects in the agro-industrial complex. Due to the recent changes in the legislation of the Russian Federation, PPP agreements can be concluded in agriculture, which is relevant in the current conditions of the sanctions struggle and the need for import substitution of agricultural products. The mechanism for implementing projects in the agro-industrial complex using the PPP mechanisms allows an investor to reduce costs in the investment phase, reduce project risks by sharing them with the state, and guarantee sales or return on the project.